Akibat Hukum Kontrak Elektronik yang dibuat dalam Bahasa Asing - Sari, Hani Puspita; Purwanto, Aldira Mara Ditta Caesar (Wajah Hukum, 2024)
Decisions to cancel foreign-language contracts in Indonesia are often linked to non-compliance with the valid terms of the contract regulated in Article 1320 KUH Perdata. The use of language in electronic contracts has become an important issue because the valid conditions of an electronic contract in Article 47 PP No. 71 Year 2019 refer to the valid contractual conditions in Article 1320 KUH Perdata. Furthermore, the absence of legal regulation over non-compliance with the obligation to use the Indonesian language in electronic contracts in Indonesia can create legal uncertainty. This research aims to determine the legal consequences regarding the validity of electronic contracts made in a foreign language in Indonesia. The research method uses normative law research with a five-month activity plan and focuses on non-Indonesian-speaking electronic contract law-related research. This research uses primary, secondary, and non-legal material and is carried out in the library. The result of this study is that although there are no special provisions on the legal consequences of foreign-language contracts, the legal effect is cancellation, cancellation by law, or even remaining in force as long as there is no bad faith or misconduct from the parties.